The Effectiveness of the Science, Technology, Engineering, Art, Mathematics, and Religious (STEAM.R) Approach on Students' Concept Understanding in Science Learning : An Analysis Based on Gender - Jelita Jelita; Mazlan Mazlan (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2023)
This study aims to analyze the effectiveness of the Science, Technology, Engineering, Art, Mathematics, and Religious (STEAM.R) approach to understanding students' concepts in learning science which are analyzed by gender. The study used a quantitative approach with the Pretest-Posttest Control Group Design. The population used was class V MI TT AL-Mubarak Langsa, totaling two classes with 34 students. While the research sample was obtained using the Simple Random Sampling technique with the lottery method, it was obtained that the female students and the male students. The instrument used was a test in the form of an essay which consisted of 5 questions. The collected data were analyzed using the t-test through SPSS 24. The result showed, based on gender, that the average post-test score of the female students was higher than that of the male students, namely 89.53 > 74.24. From the results of the hypothesis testing, it was obtained tcount > ttable, namely 5.82 > 2.04, with a significant value of 0.00 <0.05, so Ha was accepted, and H0 was rejected. Therefore, it was concluded that the Science, Technology, Engineering, Art, Mathematics, Religious (STEAM.R) approach was significantly effective in understanding students' science learning concepts.